Legal Protection for Police Officers in Handling of Labour Demonstrations - Ra’af Abdi Pandua; Suwarno Abadi (Journal of Law, Politic and Humanities, 2025)
Labour demonstrations often involve social tensions that pose legal risks for police officers. This study aims to analyse the implementation of legal protection for police officers handling labour demonstrations in Surabaya. The research employs a normative juridical method, utilising statutory, conceptual, and case approaches. The findings reveal that police officers' understanding of legal boundaries in managing demonstrations needs improvement, and challenges persist in ensuring effective legal protection. Therefore, this study recommends enhancing human rights-based training, developing clear internal policies on the use of force, and providing proactive legal support for police officers. These measures are expected to minimise the risk of criminalisation against officers acting in accordance with procedures and to enhance professionalism in handling labour demonstrations.